The Influence of Digital Literacy and Social Media Utilization on the Marketing Performance of E-Commerce-Based MSMEs in Indonesia - Lestari, Dewi Ayu; Setyawan, Rachmat; Wibisono, Gunawan; Abidin, Muhammad Zainal (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a major contributor to Indonesia's economy, but they still struggle to adapt to the digital and social media environments. The thrust of this research stems from the observation that, despite e-commerce being a clear-cut, wide-open opportunity for MSME activity, the general level of digital literacy and social media optimization among MSMEs is quite low. This study aims to examine how digital literacy and social media use influence marketing performance among e–commerce–based MSMEs in Indonesia. A mixed-method explanatory sequential approach was used in the study, which involved a quantitative survey of 150 MSMEs and in-depth interviews with 15 MSME owners. Quantitative data were analyzed using multiple linear regression, and qualitative data were examined through thematic analysis. This data indicates that digital literacy (β = 0.312; p < 0.05) and social media use (β = 0.428; p < 0.05) have significant effects on marketing performance, with an R² value of 0.56. Social media is the dominant factor in expanding market reach, while digital literacy improves MSMEs' capacity to manage technology-based marketing. The main contribution of the study is the joint analysis of digital literacy and social media, which have mostly been studied separately in prior research. The findings showed that digital literacy should be seen as the foundation, while social media is the primary tool for marketing. In practice, the research offers recommendations for MSMEs, policymakers, and business facilitators on designing integrated training programs that combine digital skills with online promotion strategies.